Treatment, Reintegration, and Quality of Prison Life: Perception by Inmates - Barquín, Jesús (International journal of offender therapy and comparative criminology, 2019)
This article inquires into the validity of the hypothesis on which prison sentences are formally based in Spain, according to Article 25.2 of Spanish Constitution: reeducation and social reintegration of the convicted person. For this purpose, we have analyzed the current state of prison "morals" in five penitentiary facilities located in the south of Spain through a representative sample of prisoners. They have answered a questionnaire that includes, among others, some questions connected with the following two issues: (a) their relationship with prison staff, and (b) the prison environment as related to the effectiveness of their treatment in terms of their reintegration into society. This investigation will also allow to detect possible differences in the quality of prison life in the five penitentiaries analyzed.